Optimal design of solar cells grid electrodes based on quadratic curves - Yongjiang Liu; Kai Li; Bo Zhou; Xiangquan Li; Peizheng Li (Results in Engineering)
The geometric configuration of grid electrodes critically determines both the photovoltaic (PV) conversion efficiency and grid volume for solar cells. This paper presents an optimization methodology employing width-varying quadratic curves to parameterize grid electrode profiles, coupled with a comprehensive power loss model. A genetic algorithm (GA) is implemented to minimize total power loss, systematically optimizing grid designs for solar cells with 156 × 156 mm², 182 × 182 mm², and 210 × 210 mm². Compared to conventional equal-width 2-busbar configurations, the optimized quadratic-curve grid electrodes demonstrate significant improvements: conversion efficiency enhancements of 1.45 %, 1.63 %, and 1.77 % with simultaneous grid volume reductions of 11.44 %, 11.39 %, and 11.23 %, respectively. For 12-busbar architectures, more pronounced benefits were achieved, with efficiency gains reaching 4.71 %, 5.33 %, 5.87 % and remarkable volume reductions of 46.55 %, 49.42 %, 51.51 % across all cell sizes. These findings offer a possible route for improving both performance and reducing grid volume.